Nitrogen-chlorine-doped carbon-loaded cobalt monatomic catalyst and preparation method thereof
By introducing nitrogen-chlorine doping into single-atom catalysts and using molten salt-assisted method, the plane-symmetric structure is broken and asymmetric coordination nitrogen-chlorine doped carbon-supported cobalt single-atom catalysts are formed, which solves the insufficient ORR activity of the existing catalysts. The problem has significantly improved the catalytic performance.
Patent Information
- Application Number
- CN202411790191.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing single-atom catalysts with a symmetrical configuration of M-N4 plane have insufficient activity in oxygen reduction reaction (ORR), and heteroatom doping methods are difficult to accurately control, resulting in limited improvement in catalyst performance.
The carbon-supported cobalt single-atom catalyst is used to dopant nitrogen and chlorine, and prepared by molten salt assisted method, breaking the plane-symmetric structure of the single-atom catalyst to form an asymmetric coordination catalyst.
The catalytic ORR performance is significantly improved, the half-wave potential reaches 0.876V, the mass transfer limit current density reaches 5.59mA cm-2, the kinetic current density reaches 75.7mA cm-2 at 0.85V, and the Taffel slope is 49.8mV dec- 1.
Smart Images

Figure CN119481106A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical catalysis, and in particular relates to a nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst and a preparation method thereof. Background Art
[0002] Single-atom catalysts (SACs) have attracted great attention from researchers due to their fully exposed active sites, 100% atomic utilization, and high catalytic activity. Among them, atomically dispersed transition metal-anchored nitrogen-doped carbon catalysts (MNC single-atom catalysts) are considered to be promising oxygen reduction reaction (ORR) catalysts to replace platinum-based catalysts (PGMs). MNC single-atom catalysts have been widely studied, especially catalysts with a planar symmetric configuration of four nitrogen-coordinated metal sites (M-N4), which show good catalytic performance. Nevertheless, their ORR activity is still insufficient when compared with platinum-based catalysts. This is because the planar symmetric configuration of M-N4 leads to a symmetrical distribution of the electronic structure, which is not conducive to the adsorption or desorption of oxygen intermediates, so the catalytic activity of MNC single-atom catalysts is poor. And because a single active site has a linear scaling limit (SRL), that is, multiple steps are involved in the ORR pathway (such as the adsorption of oxygen on the electrode surface, etc.), each step has its own reaction energy barrier. At the same time, the patent with publication number CN 117423840A also proposes that reducing the energy barrier of a step involving an active site will usually lead to an increase in the potential barriers of other steps at the same site.
[0003] Heteroatom doping (such as P, S and Cl, etc.) is considered to be a promising approach. By regulating the type and number of coordination elements of single-atom catalysts, it is beneficial to regulate the catalytic active center, change the catalytic selectivity and catalytic activity, and better understand the structure-activity relationship between catalyst structure and catalytic activity. However, since the position of heteroatoms on the carbon substrate is difficult to accurately control, the planar symmetric structure of M-N4 is still difficult to break, which limits the further improvement of catalyst performance. In addition, the introduction of heteroatoms usually requires complex experimental steps and expensive raw materials, which will increase the production cost of the catalyst, thereby limiting its promotion in industrial applications. Some heteroatom dopants may be toxic or environmentally harmful, causing environmental or safety problems, and require strict evaluation and supervision. Summary of the invention
[0004] In view of the deficiencies of the prior art, the object of the present invention is to provide a nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst.
[0005] Another object of the present invention is to provide a method for preparing a nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst.
[0006] The purpose of the present invention is achieved through the following technical solutions.
[0007] A method for preparing a nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst comprises the following steps:
[0008] A cobalt source and a zinc source are dispersed in a first solvent to obtain a metal mixture, a nitrogen organic ligand is added to a second solvent to obtain a nitrogen organic ligand solution, the metal mixture at 50 to 70°C is added to the nitrogen organic ligand solution at 50 to 70°C under stirring, the mixture is stirred at a constant temperature until a suspended matter appears, the mixture is allowed to stand to allow the suspended matter to precipitate, the precipitate is filtered to obtain a precursor, the precipitate is washed, and the precursor is dried to obtain a precursor, the precursor and sodium chloride are mixed uniformly, ground, and pyrolyzed at 800 to 1100°C for 2 to 3 hours under an inert atmosphere (the zinc element is discharged with the tail gas, molten salt assisted method), washed, and dried to obtain a nitrogen-chlorine doped carbon-supported cobalt single atom catalyst, wherein, in terms of the molar fractions, the ratio of cobalt in the cobalt source, nitrogen in the nitrogen organic ligand, and chlorine in the sodium chloride is (1 to 2): (60 to 65): (65 to 70).
[0009] In the above technical solution, the cobalt source is cobalt acetylacetonate, the zinc source is zinc nitrate hexahydrate, the nitrogen organic ligand is dimethylimidazole, the first solvent is methanol, and the second solvent is methanol.
[0010] In the above technical solution, the ratio of the mass fraction of the cobalt source, the mass fraction of the zinc source, the volume fraction of the first solvent and the volume fraction of the second solvent is (3-4): (11-13): 150: 350, the unit of the mass fraction is g, and the volume fraction is mL.
[0011] In the above technical solution, the cobalt source and the zinc source are dispersed in a first solvent at 50 to 70° C. and stirred for 15 to 20 minutes to obtain a metal mixed solution.
[0012] In the above technical solution, the nitrogen organic ligand is added into the second solvent at 50-70° C. and stirred for 10-15 minutes to obtain a nitrogen organic ligand solution.
[0013] In the above technical solution, the constant temperature stirring time is 3 to 5 minutes.
[0014] In the above technical solution, the standing time is 10 to 12 hours.
[0015] In the above technical solution, washing is performed at least 3 times with anhydrous methanol or ultrapure water.
[0016] In the above technical solution, the grinding is at least 30 minutes.
[0017] In the above technical solution, the heating rate of the pyrolysis is 3 to 5°C / min.
[0018] In the above technical solution, the drying temperature is 60-70° C., and the drying time is 10-12 hours.
[0019] In the above technical solution, the inert atmosphere is an argon atmosphere.
[0020] The nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst obtained by the above preparation method.
[0021] The use of the above-mentioned nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst in catalyzing ORR.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The asymmetrically coordinated nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared by the present invention has a half-wave potential (E 1 / 2 ) is 0.876 V (relative to the reversible hydrogen electrode), and the mass transfer limiting current density reaches 5.59 mA cm -2 , kinetic current density (J k ) up to 75.7mA cm at 0.85V -2 , the Tafel slope is 49.8mV dec -1 Compared with commercial Pt / C and nitrogen-doped carbon-supported cobalt single-atom catalysts with a planar symmetrical structure, the catalytic ORR performance of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst of the present invention is significantly improved.
[0024] (2) The preparation method of the present invention adopts a molten salt-assisted method, which simply and accurately breaks the planar symmetrical structure of the single-atom catalyst to prepare a high-purity, asymmetrically coordinated nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst. The preparation method is simple to synthesize, low in cost, pollution-free, easy to scale up experiments, and can be used for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 X-ray diffraction patterns of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1, the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1, and the nitrogen-doped carbon catalyst prepared in Comparative Example 2;
[0026] Figure 2 are transmission electron microscopy images, (a) is the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1, (b) is the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1;
[0027] Figure 3(a) is an atomic high-resolution transmission electron microscopy image of the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1, (b) is an atomic high-resolution transmission electron microscopy image of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1, (c) is an energy-dispersive X-ray element mapping image of the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1, and (d) is an energy-dispersive X-ray element mapping image of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1;
[0028] Figure 4 (a) is the Fourier transform extended X-ray absorption fine structure spectra (FT-EXAFS) of the K absorption edge (Co K edge) of the Co element in the nitrogen-chlorine-doped carbon-supported cobalt single atom catalyst prepared in Example 1, the nitrogen-doped carbon-supported cobalt single atom catalyst prepared in Comparative Example 1, cobalt chloride, cobalt oxide, cobalt phthalocyanine and cobalt foil, and (b) is Figure 4 The fitting curve and local structure model of FT-EXAFS of the nitrogen-doped carbon-supported cobalt single atom catalyst prepared in Comparative Example 1 in (a), (c) Figure 4 (a) FT-EXAFS fitting curve and local structure model of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1;
[0029] Figure 5 It is a linear sweep voltammetry curve of a three-electrode system using a commercial Pt / C electrode, a nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1, a nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1, a nitrogen-doped carbon catalyst prepared in Comparative Example 2, and a nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst prepared in Comparative Example 3;
[0030] Figure 6 The half-wave potential (E) of the three-electrode system using the commercial Pt / C electrode, the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1, the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1, the nitrogen-doped carbon catalyst prepared in Comparative Example 2, and the nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst prepared in Comparative Example 3 is shown in FIG. 1 / 2 ) and kinetic current density (J k ) Histogram;
[0031] Figure 7 It is the Tafel slope diagram of a three-electrode system using a commercial Pt / C electrode, the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1, the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1, the nitrogen-doped carbon catalyst prepared in Comparative Example 2, and the nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst prepared in Comparative Example 3. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0033] In the following examples, cobalt phthalocyanine and cobalt chloride were purchased from Aladdin, and cobalt foil was purchased from Hefei Kejing.
[0034] In the following examples, the Nafion (5 wt %) solution is a mixture of a perfluorosulfonic acid polymer (Nafion), a lower aliphatic alcohol and water. The concentration of the perfluorosulfonic acid polymer (Nafion) in the Nafion (5 wt %) solution is 5 wt %. The Nafion (5 wt %) solution was purchased from Roan Reagent Company.
[0035] In the following embodiment, the method for preparing a working electrode comprises: weighing 10 mg of a catalyst and placing it in a centrifuge tube, adding 100 μL of deionized water, 850 μL of isopropanol and 50 μL of Nafion (5 wt %) solution in sequence, ultrasonically dispersing for 60 min to form a uniform solution, measuring 6 μL of the uniform solution with a pipette and dropping it on a glassy carbon electrode, drying it naturally to obtain a working electrode, wherein the catalyst is one of commercial Pt / C, the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1, the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1, the nitrogen-doped carbon catalyst prepared in Comparative Example 2, and the nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst prepared in Comparative Example 3.
[0036] In the following examples, the three-electrode system consists of a working electrode, a reference electrode and a counter electrode. The catalyst in the working electrode is one of commercial Pt / C, the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1, the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1, the nitrogen-doped carbon catalyst prepared in Comparative Example 2, and the nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst prepared in Comparative Example 3, the reference electrode is a Hg / HgO electrode, and the counter electrode is a graphite electrode.
[0037] In the following examples, a rotating disk device and a CHI760E electrochemical workstation were used to test the linear sweep voltammetry (LSV) curve of the three-electrode system in an oxygen-saturated 0.1M KOH aqueous solution. The test conditions were: the linear sweep rate was 5 mV·s -1 , the scanning potential interval was 0.2~1.2V (vs.RHE).
[0038] Embodiments 1 to 4
[0039] A method for preparing a nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst comprises the following steps:
[0040] The cobalt source and the zinc source were dispersed in the first solvent at 60°C, and mechanically stirred for 15 minutes to obtain a metal mixture. The nitrogen organic ligand was added to the second solvent at 60°C, and mechanically stirred for 10 minutes to obtain a nitrogen organic ligand solution. Under stirring, the 60°C metal mixture was added to the 60°C nitrogen organic ligand solution, and mechanically stirred at 60°C for 5 minutes until a suspended substance appeared. The stirring was stopped, and the mixture was allowed to stand for 12 hours to allow the suspended substance to precipitate. The precipitate was filtered to obtain a precipitate, which was washed with anhydrous methanol for 6 times, and dried in a vacuum drying oven at 70°C for 12 hours to obtain a precursor. The precursor and sodium chloride were mixed evenly, ground for 30 minutes, and dried in a tube furnace at 5°C / mi under an argon atmosphere using a molten salt-assisted method. n, and pyrolyzed at T℃ for 2h (zinc elemental substance is discharged with the tail gas), washed with ultrapure water for 3 times, and dried in a vacuum drying oven at 70℃ for 12h to obtain a nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst, wherein the cobalt source is cobalt acetylacetonate, the zinc source is zinc nitrate hexahydrate, the nitrogen organic ligand is dimethylimidazole, the first solvent is methanol, and the second solvent is methanol. In terms of molar fractions, the ratio of cobalt in the cobalt source, nitrogen in the nitrogen organic ligand and chlorine in sodium chloride is 1:63:68, and the ratio of the mass fraction of the cobalt source, the mass fraction of the zinc source, the volume fraction of the first solvent and the volume fraction of the second solvent is 3.55:12:150:350, and the units of mass fraction are g, and the units of volume fraction are mL.
[0041] The numbers and T of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalysts prepared in Examples 1 to 4 are shown in Table 1.
[0042] Table 1
[0043] Example serial number T(unit:℃) Example 1 <![CDATA[Co-N4Cl-C]]> 1000 Example 2 <![CDATA[Co-N4Cl-C-800]]> 800 Example 3 <![CDATA[Co-N4Cl-C-900]]> 900 Example 4 <![CDATA[Co-N4Cl-C-1100]]> 1100
[0044] Comparative Example 1
[0045] A method for preparing a nitrogen-doped carbon-supported cobalt single-atom catalyst (code: Co-N4-C) comprises the following steps:
[0046] Disperse the cobalt source and the zinc source in the first solvent at 60°C, stir mechanically for 15 minutes to obtain a metal mixture, add the nitrogen organic ligand into the second solvent at 60°C, stir mechanically for 10 minutes to obtain a nitrogen organic ligand solution, add the 60°C metal mixture into the 60°C nitrogen organic ligand solution under stirring, stir mechanically at 60°C for 5 minutes until a suspended substance appears, stop stirring, let stand for 12 hours to allow the suspended substance to precipitate, filter to obtain a precipitate, wash with anhydrous methanol 6 times, dry in a vacuum drying oven at 70°C for 12 hours to obtain a precursor, and heat to 1000°C at a rate of 5°C / min in a tube furnace under an argon atmosphere. It was pyrolyzed at 1000°C for 2h (zinc elemental was discharged with the tail gas), washed with ultrapure water for 3 times, and dried in a vacuum drying oven at 70°C for 12h to obtain a nitrogen-doped carbon-supported cobalt single-atom catalyst, wherein the cobalt source was cobalt acetylacetonate, the zinc source was zinc nitrate hexahydrate, the nitrogen organic ligand was dimethylimidazole, the first solvent was methanol, and the second solvent was methanol. In terms of the amount of substance, the ratio of cobalt in the cobalt source to nitrogen in the nitrogen organic ligand was 1:63, and the ratio of the mass fraction of the cobalt source, the mass fraction of the zinc source, the volume fraction of the first solvent and the volume fraction of the second solvent was 3.55:12:150:350, and the units of mass fraction were g, and the units of volume fraction were mL.
[0047] Comparative Example 2
[0048] A method for preparing a nitrogen-doped carbon catalyst (code: NC) comprises the following steps:
[0049] The zinc source was dispersed in the first solvent at 60°C, and mechanically stirred for 15 minutes to obtain a metal solution. The nitrogen organic ligand was added to the second solvent at 60°C, and mechanically stirred for 10 minutes to obtain a nitrogen organic ligand solution. Under stirring, the 60°C metal solution was added to the 60°C nitrogen organic ligand solution, and mechanically stirred at 60°C for 5 minutes until a suspended substance appeared. The stirring was stopped, and the mixture was allowed to stand for 12 hours to allow the suspended substance to precipitate. The precipitate was filtered to obtain a precipitate, which was washed with anhydrous methanol for 6 times, and dried in a vacuum drying oven at 70°C for 12 hours to obtain a precursor. The precursor was heated in a tube furnace at 5°C / min under an argon atmosphere. The temperature was raised to 1000°C at a rate and pyrolyzed at 1000°C for 2h (the zinc element was discharged with the tail gas), washed with ultrapure water for 3 times, and dried in a vacuum drying oven at 70°C for 12h to obtain a nitrogen-doped carbon catalyst, wherein the zinc source was zinc nitrate hexahydrate, the nitrogen organic ligand was dimethylimidazole, the first solvent was methanol, the second solvent was methanol, the ratio of the molar fraction of nitrogen in the nitrogen organic ligand, the mass fraction of the zinc source, the volume fraction of the first solvent and the volume fraction of the second solvent was 26:12:150:350, the unit of the molar fraction was mmol, the unit of the mass fraction was g, and the volume fraction was mL.
[0050] Comparative Example 3
[0051] A method for preparing a nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst (code: Co-NP) comprises the following steps:
[0052] The cobalt source was dispersed in the first solvent at 60°C, and mechanically stirred for 15 minutes to obtain a metal mixture. The nitrogen organic ligand was added to the second solvent at 60°C, and mechanically stirred for 10 minutes to obtain a nitrogen organic ligand solution. Under stirring, the 60°C metal mixture was added to the 60°C nitrogen organic ligand solution, and mechanically stirred at 60°C for 5 minutes until a suspended substance appeared. The stirring was stopped, and the mixture was allowed to stand for 12 hours to allow the suspended substance to precipitate. The precipitate was filtered to obtain a precipitate, washed with anhydrous methanol for 6 times, and dried in a vacuum drying oven at 70°C for 12 hours to obtain a precursor. The precursor and sodium chloride were mixed evenly, ground for 30 minutes, and dried in an argon atmosphere using a molten salt-assisted method. The temperature was raised to 1000°C at a rate of 5°C / min in a tube furnace and pyrolyzed at 1000°C for 2h, washed with ultrapure water for 3 times, and dried in a vacuum drying oven at 70°C for 12h to obtain a nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst, wherein the cobalt source was cobalt nitrate hexahydrate, the nitrogen organic ligand was dimethylimidazole, the first solvent was methanol, and the second solvent was methanol. In terms of molar fractions, the ratio of cobalt in the cobalt source, nitrogen in the nitrogen organic ligand, and chlorine in sodium chloride was 1:2.4:68, and the ratio of the mass fraction of the cobalt source, the volume fraction of the first solvent, and the volume fraction of the second solvent was 6:200:200. The units of mass fraction are g, and the units of volume fraction are mL.
[0053] The nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst prepared in Comparative Example 3 is ZIF-67. According to the literature (Zeoliticimidazolate framework-67 and its derivatives for photocatalytic applications, Coordination Chemistry Reviews 502 (2024) 215612), the nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst prepared in Comparative Example 3 has a periodic network structure of a tetrahedral skeleton.
[0054] Comparative Example 4
[0055] A method for preparing a nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst comprises the following steps:
[0056] The cobalt source is dispersed in a first solvent at 60°C, and mechanically stirred for 15 minutes to obtain a metal mixture. The nitrogen organic ligand is added to a second solvent at 60°C, and mechanically stirred for 10 minutes to obtain a nitrogen organic ligand solution. Under stirring, the 60°C metal mixture is added to the 60°C nitrogen organic ligand solution, and no suspended matter appears after mechanical stirring at a constant temperature of 60°C for 5 minutes, that is, the preparation method of Comparative Example 4 does not obtain a nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst, wherein the cobalt source is cobalt acetylacetonate, the nitrogen organic ligand is dimethylimidazole, the first solvent is methanol, and the second solvent is methanol. In terms of the amount of substance, the ratio of cobalt in the cobalt source to nitrogen in the nitrogen organic ligand is 1:63, and the ratio of the mass fraction of the cobalt source, the volume fraction of the first solvent and the volume fraction of the second solvent is 3.55:150:350, and the unit of the mass fraction is g, and the volume fraction is mL.
[0057] X-ray diffraction (XRD) tests were performed on the nitrogen-chlorine-doped carbon-supported cobalt single atom catalyst prepared in Example 1, the nitrogen-doped carbon-supported cobalt single atom catalyst prepared in Comparative Example 1, and the nitrogen-doped carbon catalyst prepared in Comparative Example 2. The results are as follows: Figure 1 As shown, the XRD patterns of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1, the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1, and the nitrogen-doped carbon catalyst prepared in Comparative Example 2 have two obvious characteristic peaks at 25.9° and 42.9°, corresponding to the (002) crystal plane and (100) crystal plane of graphite carbon, respectively. In addition, no other obvious characteristic peaks were detected in the XRD pattern, which means that the Co atoms may appear in the form of amorphous phase, atomic form, or embedded in the NC skeleton.
[0058] The nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1 and the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1 were tested by transmission electron microscopy (TEM). Figure 2 As shown by Figure 2 As shown in (a), the amorphous carbon of the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1 has a similar polyhedral structure in appearance, and the size of the polyhedral structure is similar and the size distribution is uniform. Figure 2 (b) shows that the amorphous carbon of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1 has a similar spherical structure in appearance, and the spherical structure has a similar size and a uniform size distribution. Compared with the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1, the surface of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1 is etched and peeled off by molten salt (NaCl), thereby exposing more active sites, and Figure 2 No obvious black shadow aggregation is observed in (a) and (b), which proves that Co atoms can be uniformly dispersed on the surface of the carbon substrate or incorporated into the carbon nitrogen framework and no clusters are formed on the carbon substrate.
[0059] The nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1 and the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1 were tested by atomic high-resolution transmission electron microscopy (HAADF-STEM) and energy dispersive X-ray element mapping (EDS). The results are as follows: Figure 3 As shown by Figure 3 As shown in (a) and (b), the HAADF-STEM images of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1 and the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1 have dense and isolated spot-like bright spots (bright spots are marked by circles), indicating that the atomically dispersed Co atoms are anchored on the carbon substrate. Figure 3 From (c) and (d), it can be seen that C, N and Co are uniformly dispersed on the surface of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1 and the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1, and no bright aggregation points are observed, proving that no metal clusters are formed during the Co doping process. Figure 3 (d) also shows that Cl is uniformly dispersed on the surface of the nitrogen-chlorine-doped carbon-supported cobalt single atom catalyst prepared in Example 1, proving the successful introduction of Cl.
[0060] The K absorption edge (Co K edge) of the Co element in the nitrogen-chlorine-doped carbon-supported cobalt single atom catalyst prepared in Example 1, the nitrogen-doped carbon-supported cobalt single atom catalyst prepared in Comparative Example 1, cobalt chloride, cobalt oxide, cobalt phthalocyanine and cobalt foil was tested by Fourier transform extended X-ray absorption fine structure spectroscopy (FT-EXAFS). The FT-EXAFS of cobalt oxide is as follows: Figure 4 (a) "CoO * 0.6”, the FT-EXAFS of cobalt phthalocyanine is as follows Figure 4 (a) "Co-Pc * 0.7”, the FT-EXAFS of cobalt foil is as follows Figure 4 (a) "Co foil * 0.5”, shown by Figure 4 As shown in (a), compared with cobalt phthalocyanine, the FT-EXAFS spectrum of the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1 is located at ~ The main peak at can be attributed to the Co-N bond; compared with cobalt chloride, the main peak of the Co-N bond of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1 is located at ~ It happened This is because the introduction of highly electronegative Cl atoms lengthens the bond length of the Co-N bond; no Co-Co scattering peak appears in the nitrogen-doped carbon-supported cobalt single atom catalyst prepared in Comparative Example 1 and the nitrogen-chlorine-doped carbon-supported cobalt single atom catalyst prepared in Example 1, which verifies the atomic dispersion of Co in the carbon substrate; FT-EXAFS fitting is performed based on the nitrogen-doped carbon-supported cobalt single atom catalyst prepared in Comparative Example 1 and the nitrogen-chlorine-doped carbon-supported cobalt single atom catalyst prepared in Example 1 to obtain a fitting curve (as shown in the figure "fitting"), and further obtains the local structure model of the nitrogen-doped carbon-supported cobalt single atom catalyst prepared in Comparative Example 1 and the nitrogen-chlorine-doped carbon-supported cobalt single atom catalyst prepared in Example 1, as shown in FIG. Figure 4 As shown in (b) and (c), Figure 4 From (c), it can be seen that the local structural model of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1 is composed of asymmetrically coordinated Co-N4Cl.
[0061] The catalytic oxygen reduction reaction (ORR) performance of the nitrogen-chlorine-doped carbon-supported cobalt single atom catalyst prepared in Example 1, the nitrogen-doped carbon-supported cobalt single atom catalyst prepared in Comparative Example 1, the nitrogen-doped carbon catalyst prepared in Comparative Example 2, and the nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst prepared in Comparative Example 3 were investigated respectively, and a three-electrode system was constructed for testing. The test results are as follows Figure 5 As shown, for comparison, commercial Pt / C was also tested under the same conditions.
[0062] Depend on Figure 5 The half-wave potential (E 1 / 2 ) is 0.876V (relative to the reversible hydrogen electrode), which is better than the 0.832V of the commercial Pt / C electrode (relative to the reversible hydrogen electrode), the 0.804V of the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Example 1 (relative to the reversible hydrogen electrode), the 0.738V of the nitrogen-doped carbon catalyst prepared in Example 2 (relative to the reversible hydrogen electrode) and the 0.795V of the nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst prepared in Example 3 (relative to the reversible hydrogen electrode), which has good catalytic ORR activity. In addition, the mass transfer limiting current density of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1 reaches 5.59mA cm -2 , exceeding the 5.45 mA cm of commercial Pt / C electrodes. -2 The nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1 has a peak of 4.74 mA cm -2 , the nitrogen-doped carbon catalyst prepared in Comparative Example 2 had a value of 3.44 mA cm -2 The 3.70 mA cm of the nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst prepared in Comparative Example 3 was -2This higher limiting current density seems to be due to the rapid desorption of the product (oxygen-containing intermediates produced during the test) on the working electrode containing the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1. The excellent ORR activity of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1 compared with the nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst prepared in Comparative Example 3 is also related to the participation of zinc in establishing the asymmetric coordinated Co-N4Cl structure of the catalyst.
[0063] in accordance with Figure 5 The current density shown is calculated using the KL equation to obtain the kinetic current density (J k ), the half-wave potential (E) of the three-electrode system using the commercial Pt / C electrode, the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1, the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1, the nitrogen-doped carbon catalyst prepared in Comparative Example 2, and the nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst prepared in Comparative Example 3 1 / 2 ) and kinetic current density (J k ) are integrated into a bar chart, such as Figure 6 As shown by Figure 6 It can be seen that the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1 has a higher kinetic current density (J k ), up to 75.7 mA cm at 0.85 V -2 , is a commercial Pt / C electrode (25.2 mA cm -2 ). In contrast, the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1 showed poor ORR activity. k Reduced to 4.95mAcm -2 , E 1 / 2 Smaller (0.804V).
[0064] in accordance with Figure 5 The current density shown in the figure is obtained by applying the Tafel formula and linear fitting to obtain the linear fitting slope (i.e., Tafel slope). The result is as follows Figure 7 As shown, the Tafel slope of the three-electrode system of the nitrogen-doped carbon-supported cobalt single-atom catalyst prepared in Comparative Example 1 is 59.2 mV dec -1 The Tafel slope of the three-electrode system using the nitrogen-doped carbon catalyst prepared in Comparative Example 2 is 83.3 mV dec. -1 The Tafel slope of the three-electrode system using the nitrogen-chlorine-doped carbon-supported cobalt nanoparticle catalyst prepared in Comparative Example 3 is 66.4 mV dec. -1 The Tafel slope of the three-electrode system using commercial Pt / C is 57.6 mV dec. -1The Tafel slope of the three-electrode system using the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1 is the smallest, which is 49.8 mV dec. -1 , which has the fastest reaction kinetics, reflecting that the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst prepared in Example 1 has high catalytic activity.
[0065] The nitrogen-chlorine-doped carbon-supported cobalt single-atom catalysts prepared in Examples 2 to 4 can achieve the same technical effects as the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalysts prepared in Example 1.
[0066] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for preparing a nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst, characterized in that: The following steps are involved: A cobalt source and a zinc source are dispersed in a first solvent to obtain a metal mixture, a nitrogen organic ligand is added to a second solvent to obtain a nitrogen organic ligand solution, the metal mixture at 50 to 70°C is added to the nitrogen organic ligand solution at 50 to 70°C under stirring, the mixture is stirred at a constant temperature until a suspended matter appears, the mixture is allowed to stand to allow the suspended matter to precipitate, the precipitate is filtered to obtain a precursor, the precipitate is washed, and the precursor is dried to obtain a precursor, the precursor and sodium chloride are mixed uniformly, ground, and pyrolyzed at 800 to 1100°C for 2 to 3 hours under an inert atmosphere (the zinc element is discharged with the tail gas, molten salt assisted method), washed, and dried to obtain a nitrogen-chlorine doped carbon-supported cobalt single atom catalyst, wherein, in terms of the molar fractions, the ratio of cobalt in the cobalt source, nitrogen in the nitrogen organic ligand, and chlorine in the sodium chloride is (1 to 2): (60 to 65): (65 to 70).
2. The preparation method according to claim 1, characterized in that: The cobalt source is cobalt acetylacetonate, the zinc source is zinc nitrate hexahydrate, the nitrogen organic ligand is dimethylimidazole, the first solvent is methanol, and the second solvent is methanol.
3. The preparation method according to claim 1, characterized in that: The ratio of the mass fraction of the cobalt source, the mass fraction of the zinc source, the volume fraction of the first solvent and the volume fraction of the second solvent is (3-4): (11-13): 150: 350, and the units of the mass fraction are g, and the volume fraction is mL.
4. The preparation method according to claim 1, characterized in that: The cobalt source and the zinc source are dispersed in a first solvent at 50-70° C. and stirred for 15-20 minutes to obtain a metal mixed solution.
5. The preparation method according to claim 1, characterized in that: The nitrogen organic ligand is added into the second solvent at 50-70° C. and stirred for 10-15 minutes to obtain a nitrogen organic ligand solution.
6. The preparation method according to claim 1, characterized in that: The constant temperature stirring time is 3 to 5 minutes; the standing time is 10 to 12 hours.
7. The preparation method according to claim 1, characterized in that: Wash at least 3 times with anhydrous methanol or ultrapure water.
8. The preparation method according to claim 1, characterized in that: The grinding is performed for at least 30 minutes; the heating rate of the pyrolysis is 3 to 5°C / min; the drying temperature is 60 to 70°C, and the drying time is 10 to 12 hours; and the inert atmosphere is an argon atmosphere.
9. The nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the nitrogen-chlorine-doped carbon-supported cobalt single-atom catalyst as claimed in claim 9 in catalyzing ORR.
Citation Information
Patent Citations
Preparation method and application of nitrogen-doped carbon-loaded Fe3C particle and Fe / Mn heteronuclear double-monatomic catalyst
CN117423840A
Cobalt-nitrogen co-doped porous carbon material and preparation and application thereof
CN108767272A
Cobalt monatomic loaded nitrogen-doped carbon oxygen reduction catalyst and preparation method thereof
CN111468167A
Preparation method of cobalt-nitrogen-carbon material with high electro-catalytic performance
CN116093348A
Preparation and catalytic application of nitrogen-doped carbon-loaded iron-cobalt nanoparticle bifunctional catalyst
CN116344849A
Cited By
Foamy carbon-based chlorine-nitrogen co-coordinated monatomic catalyst and application thereof in killing drug-resistant bacteria in water
CN121372502A